Secondary battery

By introducing carbon nanotubes into the positive electrode material of spinel type lithium nickel manganate and controlling its size parameters, the problem of insufficient electronic conductivity of the material is solved, and the improvement of the rate performance of the secondary battery and the consideration of high temperature stability is achieved.

CN119764522AActive Publication Date: 2025-04-04CALB GROUP CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411953535.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The spinel type lithium nickel manganate has poor electron conductivity as a positive electrode material, which makes its rate performance in secondary batteries unable to effectively meet market demand.

Method used

Carbon nanotubes are introduced as conductive agents based on spinel-type nickel-manganate, and their size parameter relationship is regulated to improve the electron conduction performance of the positive electrode material.

Benefits of technology

It significantly improves the rate performance of the secondary battery, while maintaining high stability and cycling performance in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005215383940000121
    Figure BDA0005215383940000121
  • Figure BDA0005215383940000131
    Figure BDA0005215383940000131
  • Figure BDA0005215383940000141
    Figure BDA0005215383940000141
Patent Text Reader

Abstract

The invention discloses a secondary battery, and belongs to the technical field of batteries, the secondary battery is characterized in that on the basis of taking spinel type lithium nickel manganese oxide as an active material of a positive electrode material, a carbon nanotube is introduced as a conductive agent, and meanwhile, the parameter relationship between the sizes of the spinel type lithium nickel manganese oxide and the carbon nanotube is regulated and controlled; therefore, the electron conduction performance of the positive electrode material is remarkably improved, and the high-temperature stability and the cycle performance also reach a relatively high level under the condition that the rate capability of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery. Background Art

[0002] As a high-voltage positive electrode material, spinel nickel manganese oxide has a high theoretical capacity (146mAh / g), strong structural stability and thermal stability, so it has a long cycle life and high safety performance. Therefore, it is theoretically very suitable for new energy vehicles, energy storage and other fields. However, the energy band gap width of spinel nickel manganese oxide itself is large, which makes the electronic conductivity of the material itself not high. Therefore, when it is used as a positive electrode material for secondary batteries, its achieved rate performance still cannot effectively meet market demand. Summary of the invention

[0003] The purpose of the present application is to overcome the shortcomings of the prior art and provide a secondary battery. On the basis of spinel lithium nickel manganese oxide as the active material of the positive electrode material, carbon nanotubes are introduced as a conductive agent, and the parameter relationship between the spinel lithium nickel manganese oxide and the size of the carbon nanotubes is regulated. This significantly improves the electronic conduction performance of the positive electrode material, improves the rate performance of the secondary battery, and also achieves a high level of high temperature stability and cycle performance.

[0004] To achieve the above-mentioned object, in a first aspect of the present application, the present application provides a secondary battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material and a conductive agent;

[0005] The positive electrode active material includes spinel-type lithium nickel manganese oxide;

[0006] After 100 charge and discharge cycles, the characteristic peak shift at 630nm in the Raman characteristic spectrum of the spinel nickel manganese oxide is a% compared with that before the charge and discharge cycles. The charge and discharge cycle temperature is 45°C, the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 3.5V to 4.8V;

[0007] The conductive agent includes carbon nanotubes;

[0008] The secondary battery satisfies: a / b=0.0005-0.05;

[0009] Where b is the average aspect ratio of carbon nanotubes.

[0010] In a second aspect of the present application, the present application provides an electrical device, comprising the secondary battery described in the present application, wherein the secondary battery serves as a power supply for the electrical device.

[0011] The beneficial effects of this application are:

[0012] The present application provides a secondary battery, which introduces carbon nanotubes as a conductive agent based on spinel lithium nickel manganese oxide as the active material of the positive electrode material, and at the same time regulates the parameter relationship between the spinel lithium nickel manganese oxide and the size of the carbon nanotubes, so that the electronic conduction performance of the positive electrode material is significantly improved. While the rate performance of the secondary battery is improved, the high temperature stability and cycle performance also reach a high level. DETAILED DESCRIPTION

[0013] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0014] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0015] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0016] The present application is further described below with specific embodiments:

[0017] A secondary battery comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material and a conductive agent;

[0018] The positive electrode active material includes spinel-type lithium nickel manganese oxide;

[0019] After 100 charge and discharge cycles, the characteristic peak shift at 630nm in the Raman characteristic spectrum of the spinel nickel manganese oxide is a% compared with that before the charge and discharge cycles. The charge and discharge cycle temperature is 45°C, the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 3.5V to 4.8V;

[0020] The conductive agent includes carbon nanotubes;

[0021] The secondary battery satisfies: a / b=0.0005-0.05;

[0022] Wherein b is the average aspect ratio of the carbon nanotubes, that is, the length of the carbon nanotubes / the diameter of the carbon nanotubes.

[0023] Spinel-type lithium nickel manganese oxide has a high theoretical capacity, but its conductivity is poor, which limits its application in the field of new energy vehicles and energy storage. For this reason, in this application, carbon nanotubes with high conductivity are used as conductive agents to prepare the positive electrode plates of secondary batteries. On this basis, carbon nanotubes are different from traditional graphite particle conductive agents. After compounding with positive electrode active materials, they can form a three-dimensional conductive contact network, so they have better conductivity, but their tubular structure determines that their dispersibility in the positive electrode material layer must be inferior to that of granular conductive agents. They are less dispersed, the conductive contact network structure is imperfect, and the degree of conductivity improvement is insufficient; if they are dispersed too much, it is easy to cause entanglement between materials and difficult to disperse. On the other hand, the introduction of carbon nanotubes provides a large number of electron transfer sites and paths for the positive electrode active materials in secondary batteries, but this will also increase the probability of side reactions between the positive electrode active materials and the electrolyte, especially in high temperature environments, and reduce the stability and cycle performance of secondary batteries in high temperature environments. Therefore, the present application further combines and regulates the size of spinel nickel manganese oxide and carbon nanotubes, explores the effect of high-temperature cycling on the bond energy of the Mn-O bond in spinel nickel manganese oxide (i.e., the chemical bond to which the characteristic peak of the material at 630 nm in the Raman characteristic spectrum belongs), and controls the ratio of this factor to the aspect ratio of the carbon nanotubes within a specific range. This allows the carbon nanotubes and positive electrode active materials in the positive electrode material layer of the secondary battery to have high conductivity and high dispersibility when the secondary battery is in use, while maintaining the probability of side reactions between the positive electrode active material and the electrolyte in a high temperature environment within a relatively low range, taking into account both ideal rate performance and high temperature stability and cycle performance.

[0024] In some embodiments, a / b=0.0005, 0.0008, 0.001, 0.0013, 0.0015, 0.002, 0.0025, 0.0028, 0.003, 0.0035, 0.004, 0.0045, 0.005, 0.0055, 0.006, 0.0065, 0.007, 0.01, 0.02, 0.025, 0.03, 0.04, 0.05, or any two of the range values.

[0025] More preferably, a / b=0.0013-0.0028.

[0026] In the secondary battery described in the present application, the characteristic peak of spinel nickel manganese oxide at 630nm in the spectrum during Raman detection represents its Mn-O bond, and the size of the offset after the cycle indicates the strength of the Mn-O bond in the material, that is, the strength of the structural stability of the material. When the structural stability is poor, the material is prone to side reactions at high temperatures, but if the structural stability is too good, the efficiency of ions during cyclic deintercalation will become low, so it is necessary to maintain a suitable range; the aspect ratio of the carbon nanotubes affects the integrity and uniformity of the conductive network formed when it is compounded with the positive electrode active material. When the relationship between the two is constructed, it is found that when the ratio of the two falls within the above-mentioned preferred range, the secondary battery can take into account the good conductivity and high stability of the positive electrode material, and the better dispersion of the conductive agent carbon nanotubes in the positive electrode material, so that the electrochemical performance of the secondary battery is better.

[0027] In some embodiments, a=0.5-5%.

[0028] Further preferably, a=0.5%, 1%, 1.01%, 1.2%, 1.5%, 1.8%, 1.99%, 2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, or any two of the range values.

[0029] More preferably, a=1.5-2%.

[0030] As described above, the magnitude of the Raman characteristic peak offset a% of the spinel nickel manganese oxide at 630nm after cycling is related to the structural stability and ion / electron conduction efficiency of the spinel nickel manganese oxide when used as a positive electrode active material in combination with carbon nanotubes. Carbon nanotubes with different average aspect ratios are matched at different offsets to meet the a / b range requirements. The secondary battery prepared from the spinel nickel manganese oxide can perform well in rate performance and high temperature stability. When preferably within the above range, it can be further compounded with carbon nanotubes to achieve good high electrolyte wettability and ion deintercalation activity. At the same time, the probability of side reactions with the electrolyte can also be maintained at a low level, so that the secondary battery has better cycle performance at high temperatures.

[0031] It should be noted that

[0032] The test method of a is as follows: the secondary battery is disassembled, 10 6cm×7.5cm positive electrode sheets are taken, the positive electrode active material layer powder on the surface of 5 positive electrode sheets is scraped and soaked in DMC for 30 minutes, and then dried at a temperature of 45°C for 30 minutes to obtain treated powder I; the obtained treated powder I is subjected to configuration analysis of the prepared material using a confocal micro-Raman spectrometer RM2000 produced by Renishaw Company of the United Kingdom, and the test conditions are: the wavelength of the laser is 532nm, and the spectrum scanning range is 100cm -1 ~1000cm -1 , the initial Raman spectrum of the unprocessed powder was obtained, and the 630cm -1 The specific position of the peak characterizing the Mn-O bond nearby is L1; the remaining 5 positive electrode sheets are assembled into a lithium half-battery for cycle testing, the disassembled positive electrode sheet is used as the positive electrode, the lithium sheet is used as the negative electrode, and a PE film with a thickness of 15μm is used as a separator. The separator is placed between the positive electrode and the negative electrode to assemble into a single-chip battery cell, and the single-chip battery cell is placed in an aluminum-plastic film, and an electrolyte is injected with an injection volume of 3mL. After vacuum packaging, it is allowed to stand for 24h to obtain a single-chip battery; wherein the electrolyte formula is a mixture of ethylene carbonate, dimethyl carbonate and diethyl carbonate in a volume ratio of 5:3:2, and lithium hexafluorophosphate is added to prepare an electrolyte with a lithium hexafluorophosphate concentration of 1mol / L; the single-chip battery is charged to 4.8V at 0.33C, left to stand for 10min, and then discharged to 3.5V at 0.33C, The fixed capacity was cycled for 2 cycles; the fixed capacity single-chip battery was charged to 4.8V at a rate of 1C at a temperature of 45°C, and after standing for 10 minutes, it was discharged to 3.5V at a rate of 1C. After 100 cycles of charging and discharging at 1C, the single-chip battery was disassembled, the positive electrode sheet after the cycle was taken out, the positive electrode active material layer powder on the surface of the positive electrode sheet after the cycle was scraped and soaked in DMC for 30 minutes, and then dried at a temperature of 45°C for 30 minutes to obtain treated powder II; the obtained treated powder II was subjected to configuration analysis of the prepared material using a confocal micro-Raman spectrometer RM2000 produced by Renishaw, UK. The test conditions were: the wavelength of the laser was 532nm, and the spectral scanning range was 100cm -1 ~1000cm -1 , the initial Raman spectrum of the treated powder II was obtained, and the 630cm -1 The specific position of the peak representing the Mn-O bond nearby is L2, and a is calculated according to the formula 100%×|L2-L1| / L1.

[0033] In some embodiments, a is regulated by the sintering temperature of spinel nickel manganese oxide during preparation, but is not limited to this. Those skilled in the art can further achieve the regulation of a by regulating other schemes such as raw material selection and ball milling process conditions according to actual conditions.

[0034] In some embodiments, the spinel type lithium nickel manganese oxide includes LiNi x Mn y O4, where 0<x≤0.5, y=2-x.

[0035] In some embodiments, the carbon nanotubes include at least one of single-walled carbon nanotubes, modified single-walled carbon nanotubes, multi-walled carbon nanotubes, and modified multi-walled carbon nanotubes.

[0036] It should be noted that the carbon nanotubes described in the present application can be commercially available or homemade. Those skilled in the art should be aware that the carbon nanotubes obtained from different sources or preparation methods have different aspect ratios. Therefore, suitable types can be selected according to actual needs for compounding with spinel nickel lithium manganese oxide. As long as the secondary battery meets the range of a / b=0.0005~0.05 and achieves the expected technical effect, there is no restriction.

[0037] In some embodiments, b=100-1000.

[0038] Further preferably, b is a range value of one or any two of 100, 200, 250, 300, 400, 500, 600, 700, 710, 750, 780, 800, 850, 900, 1000.

[0039] More preferably, b=700-800.

[0040] It should be noted that the test method for the average aspect ratio b of the carbon nanotubes described in the present application is: disassemble the secondary battery, then scrape out the positive electrode material layer on the obtained positive electrode plate, soak the obtained mixed powder in DMC for 30 minutes, and then dry it at a temperature of 45°C for 30 minutes, then use FEI TF20 transmission electron microscope energy spectrometer to identify the carbon nanotubes in the material at a magnification of 5000 and randomly select 3 to 5 carbon nanotubes in the upper, lower, left, right and middle areas of the image, a total of 25, then magnify it to 50,000 times and use mapping software to measure the diameter and length of the carbon nanotubes at this magnification, the test sites are the front end, middle and rear end of a single carbon nanotube, and the test values ​​are averaged; calculate the aspect ratio of a single carbon nanotube by diameter and length, count the aspect ratios of all carbon nanotubes, and calculate the average value, which is b.

[0041] More preferably, the carbon nanotubes have a diameter of 2 to 20 nm and a length of 200 to 2000 nm.

[0042] The average aspect ratio of carbon nanotubes reflects the morphology of the material to a certain extent. The smaller the aspect ratio, the closer the morphology of the carbon nanotubes is to particles and the higher the dispersibility is, but the integrity of the conductive network built with the positive electrode active material is lower, and the number of transmission paths and transmission sites provided for ions / electrons is smaller. The larger the aspect ratio, the better the overall three-dimensional structure of the material after compounding with the positive electrode active material, the better the conductivity, but the lower the dispersibility, and it also provides sites for side reactions between the electrolyte and the positive electrode material. Therefore, it is necessary to balance the conductivity of carbon nanotubes after being introduced into secondary batteries, the dispersibility of electrode materials and the chemical stability. When the average aspect ratio of the carbon nanotubes is preferably within the above range, the comprehensive electrochemical performance of the secondary battery is better.

[0043] In some embodiments, the positive electrode plate includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material and carbon nanotubes, and the mass percentage of the carbon nanotubes in the positive electrode material layer is 0.05-1%.

[0044] Further preferably, the mass percentage of the carbon nanotubes in the positive electrode material layer is 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.55%, 0.6%, 0.65%, 0.7%, 0.75%, 0.8%, 0.85%, 0.9%, 0.95%, 1% or any two of the range values.

[0045] In some embodiments, the positive electrode active material further includes a doping element, and the doping element includes at least one of Al, Zr, P, and W.

[0046] When spinel nickel manganese oxide, a 5V material, is used as the positive electrode active material of a secondary battery, introducing certain doping elements can further improve its balance between structural stability and conductivity, so that the secondary battery can have better cycle stability and charge and discharge efficiency during cycling.

[0047] In some embodiments, the positive electrode active material further includes a coating layer, and the coating layer includes at least one of Al2O3, Li3P, ZrO2, and TaO2.

[0048] The positive electrode active material is coated with the coating layer, which can further effectively inhibit the side reaction activity of spinel nickel lithium manganese oxide and the electrolyte, and improve the stability of the secondary battery at high temperature.

[0049] In some embodiments, the secondary battery includes an electrolyte including a solvent and a lithium salt.

[0050] In some embodiments, the solvent includes at least one of a carbonate solvent, a carboxylate solvent, an ether solvent, a sulfone solvent, a nitrile solvent, and a phosphate solvent.

[0051] Exemplarily, the carbonate solvent includes but is not limited to at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent includes but is not limited to at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent includes at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent includes at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent includes at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent includes at least one of trimethyl triphosphate and triethyl phosphate.

[0052] Further preferably, the solvent may also include but is not limited to at least one of fluorinated derivatives of carbonate solvents, fluorinated derivatives of carboxylate solvents, fluorinated derivatives of ether solvents, fluorinated derivatives of sulfone solvents, fluorinated derivatives of nitrile solvents, and fluorinated derivatives of phosphate solvents.

[0053] In some embodiments, the lithium salt includes at least one of lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium perchlorate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium difluorooxalatoborate, lithium trifluoromethanesulfonate, lithium bis(trifluoromethanesulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium difluorobis(oxalatophosphate), lithium tetrafluorooxalatophosphate, and the like.

[0054] Further preferably, the concentration of the lithium salt in the electrolyte is 0.8 to 2.5 mol / L.

[0055] Further preferably, the concentration of the lithium salt in the electrolyte is in the range of one or any two of 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, and 2.5 mol / L.

[0056] The secondary battery described in the present application is compounded with various suitable types of solvents and lithium salts according to actual needs, and the concentration of the lithium salt is adjusted at the same time. As long as the normal use effect can be achieved, it is not limited by the described solution.

[0057] In some embodiments, the positive electrode material layer further includes a binder.

[0058] Further preferably, the binder includes polyvinylidene fluoride.

[0059] In some embodiments, the secondary battery includes a negative electrode sheet, and the negative electrode sheet includes a negative electrode active material.

[0060] In some embodiments, the negative electrode active material includes at least one of a carbon-based material, a silicon-based material, and a silicon-carbon composite material.

[0061] In some embodiments, the positive electrode plate further includes a current collector, at least one side of the current collector is provided with a positive electrode material layer, and the positive electrode material layer includes a positive electrode active material.

[0062] In some embodiments, the negative electrode plate further includes a current collector, at least one side of the current collector is provided with a negative electrode material layer, and the negative electrode material layer includes a negative electrode active material;

[0063] Further preferably, the negative electrode material layer comprises a negative electrode material, a binder, a thickener and a conductive agent.

[0064] The present invention is further described below with specific examples, which are not to be construed as limiting the scope of the present invention:

[0065] The preparation method of the positive electrode sheet in the present invention is:

[0066] The lithium source, nickel source and manganese source are mixed at a target molar ratio, and mixed with zirconium oxide balls with a diameter of 0.6-1.0 mm at a ball-to-material ratio of 5:1-8:1, and ball-milled at a rotation speed of 1700-2300 rpm for 5-12 hours. The ball-milled mixture is then calcined at a temperature of 700-1200°C for 6-24 hours and then cooled to room temperature to obtain spinel lithium nickel manganese oxide.

[0067] The lithium source options include: lithium carbonate, lithium hydroxide;

[0068] Nickel source selection: nickel hydroxide, nickel carbonate, nickel oxide;

[0069] Manganese source selection: manganese hydroxide, manganese carbonate, manganese oxide;

[0070] The conductive agent and the binder of the positive electrode active material are dispersed in N-methylpyrrolidone (NMP) in a mass ratio of (94.0-99.85):(0.05-1.0):(0.1-5.0) to obtain a positive electrode slurry, and the positive electrode slurry is coated on an aluminum foil to obtain an aluminum foil with the positive electrode slurry coated on the surface; after drying, the aluminum foil is rolled and cut to obtain a positive electrode sheet.

[0071] The binder is selected from polytetrafluoroethylene or polyvinylidene fluoride.

[0072] The conductive agent is selected from one or more of conductive carbon black, acetylene black and carbon nanotubes.

[0073] Method for preparing negative electrode sheet

[0074] The negative electrode material, the binder and the conductive agent are dispersed in deionized water according to a mass ratio of (93.0-99.8):(0.1-2.0):(0.1-5.0) to obtain a negative electrode slurry, and the negative electrode slurry is coated on a copper foil; after drying, cold pressing and cutting, the negative electrode sheet is obtained.

[0075] The negative electrode main material is selected from one or more of natural graphite, artificial graphite, soft carbon and hard carbon;

[0076] The binder is selected from one or more of polyacrylic acid (PAA), styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC);

[0077] The conductive agent is selected from conductive carbon black and / or carbon nanotubes.

[0078] Preparation of electrolyte:

[0079] The solvent and the lithium salt are mixed in a mass ratio of (98-99.99):(0.01:2) to obtain an electrolyte.

[0080] The solvent is selected from at least one of carbonate solvents, carboxylate solvents, ether solvents, sulfone solvents, nitrile solvents, and phosphate solvents.

[0081] The carbonate solvent is selected from at least one of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and ethyl methyl carbonate (EMC); the carboxylate solvent is selected from at least one of ethyl acetate, methyl formate, and 1,4-butyrolactone; the ether solvent is selected from at least one of dimethyltetrahydrofuran, tetrahydrofuran, and 1,2-dimethoxyethane; the sulfone solvent is selected from at least one of methyl sulfone and dimethyl sulfoxide; the nitrile solvent is selected from at least one of propionitrile, butyronitrile, 1-(2-cyanoethyl)pyrrole, and 1,3,6-hexanetrinitrile; the phosphate solvent is selected from at least one of trimethyl triphosphate and triethyl phosphate.

[0082] The lithium salt is selected from at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP), and lithium tetrafluorooxalatophosphate (LiTFOP).

[0083] Example 1

[0084] A secondary battery, the preparation method comprising the following steps:

[0085] (1) Preparation of positive electrode active materials: Li2CO3, NiCO3 and MnO2 were mechanically mixed by ball milling at 2000 rpm according to the stoichiometric ratio for 8 h, and then heated to T℃ in air atmosphere for calcination for 3 h and then naturally cooled to room temperature to obtain spinel lithium nickel manganese oxide LiNi 0.5 Mn 1.5 O4;

[0086] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 98:0.65:1.35, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet; the average length of the carbon nanotubes is cnm, the average diameter is dnm, and the carbon nanotubes are multi-walled carbon nanotubes;

[0087] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water according to a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet; the negative electrode material is graphite;

[0088] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0089] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF6 is added and dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L;

[0090] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0091] The constant capacity step is: charging the secondary battery to 4.6V at 0.33C, and then charging it to an upper limit cut-off voltage of 4.8V at a PC rate.

[0092] The specific process parameters are shown in Table 1;

[0093] The size parameters of the carbon nanotubes in the positive electrode plate and the characteristic parameters of the spinel lithium nickel manganese oxide are shown in Table 1.

[0094] Embodiments 2 to 18

[0095] A secondary battery, which is different from Example 1 only in that the preparation process parameters of the positive electrode active material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0096] Examples 19 to 22

[0097] A secondary battery, which is different from Example 1 only in that the preparation process parameters of the positive electrode active material and the characteristic parameters of the obtained positive electrode material are different. Specifically, the positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 98:1:1, and the rest is as shown in Table 1.

[0098] Embodiment 23

[0099] A secondary battery, the preparation method comprising the following steps:

[0100] (1) Preparation of positive electrode active materials: Li2CO3, NiCO3 and MnO2 were mechanically mixed by ball milling at 2000 rpm according to the stoichiometric ratio for 8 h, and then heated to T℃ in air atmosphere for calcination for 3 h and then naturally cooled to room temperature to obtain spinel lithium nickel manganese oxide LiNi 0.8 Mn 1.2 O4;

[0101] The specific process parameters are shown in Table 1;

[0102] (2) Preparation of positive electrode sheet: The positive electrode active material, the conductive agent carbon nanotubes and the binder polyvinylidene fluoride are dispersed in N-methylpyrrolidone in a mass ratio of 98:0.65:1.35, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector aluminum foil, and then dried, cold pressed and cut to obtain the positive electrode sheet; the average length of the carbon nanotubes is cnm, the average diameter is dnm, and the carbon nanotubes are multi-walled carbon nanotubes;

[0103] (3) Preparation of negative electrode sheet: The negative electrode active material, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose, and the binder styrene butadiene rubber are dispersed in water according to a mass ratio of 96.4:1:1.2:1.4, and the slurry is prepared by vacuum stirring, and then coated on both sides of the current collector copper foil, and then dried, cold pressed, and cut to obtain the negative electrode sheet; the negative electrode material is graphite;

[0104] (4) Selection of diaphragm: Choose a commercially available polyethylene diaphragm with a thickness of 15 μm;

[0105] (5) Preparation of electrolyte: Ethylene carbonate and dimethyl carbonate are mixed in a volume ratio of 1:1 to obtain an organic solvent, and lithium salt LiPF6 is added and dissolved in the mixed organic solvent to prepare an electrolyte with a concentration of 1 mol / L;

[0106] (6) The positive electrode sheet, the separator, and the negative electrode sheet are stacked and wound in order to form a battery cell, and the battery cell is placed in an outer packaging shell, injected with electrolyte after drying, and vacuum packaged, left to stand for 24 hours, formed, and constant capacity to obtain the secondary battery.

[0107] The constant capacity step is: charging the secondary battery to 4.6V at 0.33C, and then charging it to an upper limit cut-off voltage of 4.8V at a PC rate.

[0108] The size parameters of the carbon nanotubes in the positive electrode plate and the characteristic parameters of the spinel lithium nickel manganese oxide are shown in Table 1.

[0109] Comparative Examples 1 to 6

[0110] A secondary battery, which is different from Example 1 only in that the preparation process parameters of the positive electrode active material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0111] Comparative Examples 7 to 8

[0112] A secondary battery, which is different from Example 23 only in that the preparation process parameters of the positive electrode active material and the characteristic parameters of the obtained positive electrode material are different, as shown in Table 1.

[0113] Table 1

[0114]

[0115]

[0116] Effect example

[0117] The positive electrode materials and secondary batteries obtained in each embodiment and comparative example were tested as follows:

[0118] (1) High temperature cycle performance test: The secondary batteries obtained in each embodiment and comparative example were preliminarily charged to 4.8V at 25°C using a LAND charge and discharge system at a constant current and a charge rate of 0.33C; then discharged to 3.5V at a constant current and a rate of 0.33C for 2 cycles; then placed in a 45°C environment and charged and discharged 100 times at a rate of 1C / 1C using the same system at the same operating voltage, i.e., a cut-off voltage of 3.5V and 4.8V, and the discharge capacity at each cycle number was counted, and finally the high temperature cycle capacity retention rate (%) was calculated as follows: discharge capacity of the secondary battery after the 100th 1C / 1C rate cycle / discharge capacity of the secondary battery in the first 1C / 1C rate cycle;

[0119] (2) High-temperature storage gas generation performance test: The secondary batteries obtained in each embodiment and comparative example were pre-charged and discharged using a LAND charging and discharging system at room temperature.

[0120] Charge at a constant current of 0.33C to an upper limit voltage of 4.8V, charge at a constant voltage until the current is less than or equal to 0.05C, then discharge at a constant current to 3.5V, with a rate of 0.33C. After 2 cycles, use the drainage method to test the volume of the battery, recorded as V0. Then place the battery in a 45°C oven for a period of time and take it out. After the battery temperature drops to room temperature 25°C, use the drainage method to test the volume of the battery again, recorded as V1. Calculate the gas production at 45°C storage according to the following formula:

[0121] Gas production at 45°C storage = (V1-V0) / battery capacity.

[0122] The specific method of testing the volume of the battery by the drainage method is as follows:

[0123] 1) Add an appropriate amount of pure water into the container and use a density meter to test its density ρ and record it;

[0124] 2) Place the aforementioned container on a balance and peel it (peeling is performed before testing each battery cell);

[0125] 3) Immerse the battery body and the tabs together in pure water to ensure that the battery does not contact the container wall. After stabilization, read and record the data. The data before the battery is stored in the oven is recorded as T0, and the data after the battery is stored in the oven is recorded as T0;

[0126] 4) Turn off the balance and seal the container to prevent the reagent from evaporating.

[0127] V1-V0 is calculated according to the following formula: V1-V0=T0 / ρ-T1 / ρ.

[0128] The test results are shown in Table 2.

[0129] Table 2

[0130]

[0131]

[0132] From Table 2 we can see that:

[0133] (1) In the secondary battery described in the present application, by arranging spinel lithium nickel manganese oxide and conductive carbon nanotubes on the positive electrode plate, and at the same time synergistically regulating the Mn-O bond energy of the spinel lithium nickel manganese oxide at high temperature and the aspect ratio of the carbon nanotubes, not only can the compatibility and dispersibility of the positive electrode active material and the conductive agent be improved, but also the probability of side reactions between the positive electrode active material and the electrolyte in a high temperature environment can be reduced to a lower level. The capacity retention rate of the secondary battery after 100 cycles at high temperature can reach 80% or more, and the high-temperature storage gas production can be within 25 mL, and the electrochemical performance in a high temperature environment is excellent. In contrast, the size of the secondary batteries or carbon nanotubes obtained in each comparative example is too large or too small, or the Mn-O bond energy of the spinel nickel manganese oxide at high temperature is too high or too low, or the degree of regulation of the two is improper, resulting in a / b failing to meet the range of 0.0005 to 0.05, and its high-temperature cycle capacity retention rate is basically maintained at around 75%, and the high-temperature gas production is relatively high, reaching a maximum of 42 mL, and the high-temperature performance and even the safety cannot meet the standards.

[0134] (2) According to Examples 1 to 18, it can be seen that due to the change in the strength of the Mn-O bond of the spinel lithium nickel manganese oxide in the positive electrode sheet of the secondary battery, that is, when the structural stability of the material changes, the probability of side reactions occurring at high temperatures and the efficiency of ion cycle deintercalation will also change; on the other hand, the aspect ratio of the carbon nanotubes affects the integrity and dispersion uniformity of the conductive network formed when they are compounded with the positive electrode active material. When the relationship between the two is constructed, the change in the ratio of the two will also directly affect the high-temperature electrochemical performance of the secondary battery. When a / b is further preferably in the range of 0.0013 to 0.0028, the high-temperature cycle capacity retention rate of the secondary battery can be maintained at more than 85%, and the gas production can be maintained within 15 mL. When a is preferably 1.5 to 2%, and b is preferably 700 to 800, the electrochemical performance of the secondary battery can be further improved, the cycle capacity retention rate at high temperature reaches more than 90%, and the gas production is less than 10 mL.

Claims

1. A secondary battery, characterized in that: The invention comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material and a conductive agent; The positive electrode active material includes spinel-type lithium nickel manganese oxide; After 100 charge and discharge cycles, the characteristic peak shift at 630nm in the Raman characteristic spectrum of the spinel nickel manganese oxide is a% compared with that before the charge and discharge cycles. The charge and discharge cycle temperature is 45°C, the charge and discharge rate is 1C / 1C, and the charge and discharge cut-off voltage is 3.5V to 4.8V; The conductive agent includes carbon nanotubes; The secondary battery satisfies: a / b=0.0005-0.05; Where b is the average aspect ratio of carbon nanotubes.

2. The secondary battery according to claim 1, characterized in that: The a / b=0.0013~0.0028.

3. The secondary battery according to claim 1, characterized in that: The a=0.5-5%.

4. The secondary battery according to claim 1, wherein: The b=100-1000.

5. The secondary battery according to claim 1, characterized in that: The carbon nanotube has a diameter of 2 to 20 nm and a length of 200 to 2000 nm.

6. The secondary battery according to claim 1, characterized in that: The positive electrode plate comprises a positive electrode material layer, the positive electrode material layer comprises a positive electrode active material and carbon nanotubes, and the mass percentage of the carbon nanotubes in the positive electrode material layer is 0.05-1%.

7. The secondary battery according to claim 1, characterized in that: The carbon nanotubes include at least one of single-walled carbon nanotubes, modified single-walled carbon nanotubes, multi-walled carbon nanotubes, and modified multi-walled carbon nanotubes.

8. The secondary battery according to claim 1, characterized in that: The positive electrode active material further includes a doping element, and the doping element includes at least one of Al, Zr, P, and W.

9. The secondary battery according to claim 1, characterized in that: The positive electrode active material further includes a coating layer, and the coating layer includes at least one of Al2O3, Li3P, ZrO2, and TaO2.

10. An electrical device, characterized in that: The invention comprises the secondary battery according to any one of claims 1 to 9, wherein the secondary battery is used as a power supply for the electrical device.

Citation Information

Patent Citations

  • Preparation method of carbon nanotube-graphene modified lithium manganate cathode material

    CN104485451A

  • Lithium-ion secondary battery

    CN106252712A

  • Spinel type lithium nickel manganese oxide, preparation method thereof and lithium ion battery

    CN113707875A

  • Positive electrode material, positive electrode plate, secondary battery, battery module, battery pack, and electrical apparatus

    US20240274811A1